Perancangan Kursi dengan Konsep Space-Saving Furniture dan Eco-Design pada Apartemen di DKI Jakarta - Pringgo Widyo Laksono; Bambang Suhardi; Emirsyah Muhaimin (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
Limited space in apartment force the resident to use their space effectively and efficiently. The resident need a furniture that can save the space and easy to be move. Furthermore, the furniture’s material has to be eco-friendly in order to make a better environment for the future generation. One of the common furniture is chair. Based on survey of 20 apartment resident in Jakarta, the resident stated 12 feature of chair: easy to move (15%); eco-friendly material (35%); foldable (25%), hangable (15%), simple (30%), storage (30%), space-saving (35%), durable (10%), multifunction (25%), comfortable (50%), provide backrest (10%), and aesthetic (5%). These costumer statements have generate 4 design concept that can fulfil the requirements. First concept is a storage chair with HDPE material. Second concept is a storage chair with plywood material. Third concept is an easy-saving chair with HDPE material. Fourth concept is an easy-saving chair with plywood material.